Research on Accounts Receivable Management of Small and Medium-Sized Food Enterprises in China:Taking Suzhou Chaojie Company as an Example - Sun, Lei (Transactions on Economics, Business and Management Research, 2024)
The operation and development of small and medium-sized food enterprises in China can be regarded as a relatively stable existence.After all, no matter how the society develops, the first step for people is to solve the problem of eating.Even if restaurants are frequently shut down and deliveries are blocked, food companies should not face a crisis of survival.However, the main food condiment of the super Jie company sales decline in recent years is not very large, but the company has suffered substantial losses, and even faced the risk of bankruptcy.This paper mainly based on the food enterprise Chaojie company's accounts receivable status in recent years, firstly analyzed the company's accounts receivable scale, development trend and accounts receivable management status.Then analyze the causes of the bad situation of accounts receivable and put forward reasonable and legal countermeasures and specific suggestions.It is hoped that this paper can improve the daily management of accounts receivable of Chaojie Company and optimize the daily management structure of the enterprise.Finally, it is hoped that through the study of Chaojie Company, it can provide optimization suggestions for China's small and medium-sized food enterprises in the management of accounts receivable.